(God) After Auschwitz : Tradition and Change in Post-Holocaust Jewish Thought. - Braiterman, Zachary (Princeton University Press, 2001)
The impact of technology-enhanced mass death in the twentieth century, argues Zachary Braiterman, has profoundly affected the future shape of religious thought. In his provocative book, the author shows how key Jewish theologians faced the memory of Auschwitz by rejecting traditional theodicy, abandoning any attempt to justify and vindicate the relationship between God and catastrophic suffering. The author terms this rejection "Antitheodicy," the refusal to accept that relationship. It finds voice in the writings of three particular theologians: Richard Rubenstein, Eliezer Berkovits, and Emil.